How Renewable Energy Consumption Affects Economic Growth in ASEAN: The Role of Banking Sector - Ha, Tran Manh; Ngan, Nguyen Thi Thuy (International Journal of Energy Economics and Policy, 2026)
This study investigates the impact of renewable energy consumption on economic growth in ASEAN countries and the moderating role of banking sector development during the period 2000–2022, using a Multi-way Fixed Effects (MWFE) regression model. The empirical results show that renewable energy consumption has a negative impact on economic growth in ASEAN. However, this relationship becomes less negative due to the moderating effect of banking sector development. The study also finds that internal conditions within ASEAN countries have contributed to the inverse effect of renewable energy consumption on economic growth. This study is the first to examine the regulatory role of bank development in the relationship between renewable energy consumption and economic growth. Based on these findings, the authors explain the underlying causes and suggest several solutions to promote renewable energy development in the region.